MALAYSIAN CAFÉ CULTURE: THE RELATIONSHIP BETWEEN CUSTOMER EXPERIENCE AND CUSTOMER SATISFACTION TOWARDS CONTEMPORARY Cafés - Huang, Liew (PEOPLE: International Journal of Social Sciences, 2017)
This study explored the modernity of Malaysian local coffee culture context. Coffee culture was practiced globally played an important role in the city landscape, specifically in Klang Valley, Malaysia. The researcher showed that the concept of experiential marketing was used in many hospitality organizations such as contemporary cafés, in order to create customer experience. Therefore, this paper addressed the importance of customer experience by highlighting both functional and emotional elements in customer values. This study also emphasized on the concept of “third place” which appealed to be occurred in the contemporary cafés. To conduct this study, a quantitative approach by using web survey technique was applied to 80 respondents. This research determined the effects of customer experience in terms of place attachment and customer value. The conceptual framework of customer experience was taken to examine the association with customer satisfaction. Customer satisfaction is derived in the positive feelings resulting from the patrons such as customer delight and loyalty.